Teaching palaeography on the web. - Twycross, M (Literary & Linguistic Computing, 1999)
The article discusses the use web in teaching palaeography. It presents the Teaching and Learning Technology (TLTP) initiative which concentrate in software development projects that can have a wide application. It mentions the early development stages of electronic palaeography course in which Micrografix Photomagic application was installed in all computer laboratories of Lancaster University. It adds the procedures on using Adobe Photoshop 4.0.1 in doing an average week's assignment.